Managerial personal diversification and portfolio equity incentives - Hung, Mao-Wei; Liu, Yu-Jane; Tsai, Chia-Fen (Journal of Corporate Finance, 2012)
This paper examines the diversification choices of top managers and their implications for the levels of portfolio equity incentives as well as for firms' financial policies. Standard portfolio theory should also apply to corporate managers and therefore excessive risk exposures to the firm should create portfolio diversification incentives for the managers. We use a unique dataset from the Taiwan tax data center and construct the measures of the degree of diversification in a manager's equity portfolio that is made up of equities of other firms to capture his motives for diversifying his risk exposure to his own firm. We provide empirical evidence supporting the view that managers have a risk-reduction motive when they trade in the equities of other firms besides their own. Moreover, we document evidence that the degree of diversification in such equity portfolios also significantly affects managerial equity incentives as well as firms' financial policies. Overall, our findings confirm that managers' personal diversification can help make up for the diversification that the managers would otherwise have lost, thereby reducing the agency cost of equity incentive contracts.